Proceedings of the 25th ACM International on Conference on Information and Knowledge Management 2016
DOI: 10.1145/2983323.2983798
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Entities with Just a Little Help from You

Abstract: Linking entities like people, organizations, books, music groups and their songs in text to knowledge bases (KBs) is a fundamental task for many downstream search and mining applications. Achieving high disambiguation accuracy crucially depends on a rich and holistic representation of the entities in the KB. For popular entities, such a representation can be easily mined from Wikipedia, and many current entity disambiguation and linking methods make use of this fact. However, Wikipedia does not contain long-ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Finally, we showed that there seems to be a sweet spot in the choice of sparsity that varies depending on the dataset. We believe that the applicability of a sparsity-inducing component can extend beyond document ranking to other ranking [20,21,58], graph [13] and Web tasks [2,51,57].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we showed that there seems to be a sweet spot in the choice of sparsity that varies depending on the dataset. We believe that the applicability of a sparsity-inducing component can extend beyond document ranking to other ranking [20,21,58], graph [13] and Web tasks [2,51,57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to academic efforts, model debugging tools like [28,36], SageMaker 1 provided by Amazon are also available. Other human-in-the loop systems include [8,30] to update models and knowledge bases. However, they mostly focus on training process and do not provide a post-hoc model risk assessment.…”
Section: Related Workmentioning
confidence: 99%
“…Many research projects have entangled with the different problems described in this work, i.e. news aggregation [5,9,12,20,35], event pattern extraction [15,43], entity linking [12,19,20,23], emerging entity detection [14,17,25,30,34], event ontology population [29,42] and automatically answering journalist Ws [10,11]. However, only a few big projects are comparable to our system as end-to-end online pipelines for event detection and encoding.…”
Section: Related Workmentioning
confidence: 99%